Praca w placówce pediatrycznego leczenia paliatywnego w narracjach personelu medycznego - Gruza, Magdalena (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
Nowadays the good thing is being healthy, young and beautiful. Suffering, disease, old age and death are pushed to the margins of social life, hidden behind the closed doors of hospitals and nursing homes. A man wants do anything to get away from the situation of confrontation with the fragility of human life. However, there are still people who want to support others with professional activity. The purpose of this article is to present reports on the narrative research about working on the pediatric palliative ward and to show what medical staff is thinking about life, death and themselves.